Norms and values of the various microfinance institutions - Marek Hudon (International Journal of Social Economics Vol. 35 No. 1/2, 2008 pp. 35-48, 2008)
The paper aims to study the role of norms and values in the microfinance sector. The paper provides a combination of narrative with argument and analysis. Findings - A classification of the sector is proposed, mapping the institutions along two axes: the profit motive (profit vs not-for-profit) and the decision-making style (centralized vs un-centralized). Some microfinance institutions base their interactions on rigid norms or rules; while others are based on values. It is argued that the private sector will tend to produce the operating rules of the microfinance system while the not-for-profit institutions that are using an inclusive decision-making process are more likely to influence the ethical norms in the sector. Nevertheless, this classification is not static as recent events in South-India shows that norms, such as the interest rates, can be politically and emotionally invested to the point that they are about to become values in the sector. Originality/value - The conclusions drawn help in understanding the interactions between the various actions in microfinance. Exploiting the full range of the possibilities of those different structures may be valuable for a fully successful development in India